2012
DOI: 10.1007/s10517-012-1561-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prostatic Epithelium Basement Membrane Incompetence in the Pathogenesis of Chronic Prostatitis

Abstract: Prostatic inflammation is associated with infections penetrating through the urethra. This inflammation is treated by long courses of wide-spectrum antibiotics. However, the most frequent cause of prostatitis is Escherichia coli and other enteric flora. Electron microscopy of biopsy specimens from the prostate detected gaps in the prostatic epithelium basement membrane, their size explaining the penetration of enteric flora into the prostate. These data suggest another view on the pathogenesis of prostatitis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Literature reports that there are kind of connections between prostate hyperplasia and CP/CPPS. [7,8] At present, there is no specific therapy for this disease in modern medicine and we mainly adopt antibiotics, α-blockers, etc., however, multicenter clinical studies have shown that the curative effect of single treatment mode is limited or even invalid. [911] In addition, due to the specificity of the anatomical structure of prostate—the deeper intima of the capsule, it is easy to cause local microcirculation disturbance, blockage of blood stasis, drainage blocked.…”
Section: Introductionmentioning
confidence: 99%
“…Literature reports that there are kind of connections between prostate hyperplasia and CP/CPPS. [7,8] At present, there is no specific therapy for this disease in modern medicine and we mainly adopt antibiotics, α-blockers, etc., however, multicenter clinical studies have shown that the curative effect of single treatment mode is limited or even invalid. [911] In addition, due to the specificity of the anatomical structure of prostate—the deeper intima of the capsule, it is easy to cause local microcirculation disturbance, blockage of blood stasis, drainage blocked.…”
Section: Introductionmentioning
confidence: 99%
“…Literature reports that there are kind of connections between prostate hyperplasia and CP/CPPS. [7–8] At present, there is no specific therapy for this disease in modern medicine and we mainly adopt antibiotics, α-blockers, and so on; however, multicenter clinical studies have shown that the curative effect of single treatment mode is limited or even invalid. [911] In addition, due to the specificity of the anatomical structure of prostate – the deeper intima of the capsule, it is easy to cause local microcirculation disturbance, blockage of blood stasis, drainage blocked.…”
Section: Introductionmentioning
confidence: 99%